Aotearoa/New Zealand Starting National Evaluation Conferences - Pam Oliver; Maggie Jakob-Hoff; Chris Mullins (The Evaluation Center at Western Michigan University, 2005)
Aotearoa/New Zealand had its first national evaluation conference in September 2004. Organised by the Auckland Evaluation Group, the meeting was held at the Tauhara Centre, near Lake Taupo (central North Island).